Tommaso Campanella: su defensa de Galileo y de la libertas philosophandi - Fernández, Javier (2015)
The present article highlights and analyses the main arguments presented in favour of Galileo in the work Apologia pro Galileo (1622). Subsequently, it defends that it can be read from the text, a realist posture concerning the role of the astronomical science.